"Social food": Food literacy co-construction and distortion on social media. (August 2020) - Steils, Nadia; Obaidalahe, Zakia
Highlights: Social media users construct food literacy directly or indirectly. Users' contribution varies in depth and breadth. Contribution levels include evaluation, adaptation suggestions, procedural critiques. Distortion occurs due to judgment biases, affecting the quality of contributions. Abstract: Social media encourage the rapid spreading of food-related information and potentially act as a policy measure to improve food literacy, healthy eating and well-being. However, some authors warn about the lack of control over the quality of the shared information and the risks of knowledge distortion. The aim of this research is to understand how food literacy is co-constructed on social media and to identify the potential sources of bias, which lead to knowledge distortion. We use a netnographic approach (i.e. analysis of behavioral secondary data from social media and semi-structured interviews) to study both phenomena. Findings indicate that food literacy can be positively or negatively co-constructed in a social environment. Consumers can contribute to the construction of food literacy directly or indirectly on three levels (i.e. evaluation, adaptation suggestions and procedural critiques), which vary in depth and breadth of contribution. We further identify four types of biases, which risk affecting the quality of the co-constructed food literacy online, namely vividness, mindset, socio-cultural and cognitive dissonance bias. Findings help food policy makers to better understand how food literacy is developed outside of their control, and to identify the potential sources of knowledge distortion and how they can reduce these biases.